Solid Phase Extraction of Palladium Uusing Microspheres Containing Hexyl Benzimidazolyl Sulphide as Sorbent - Li, Cong; Huang*, Zhangjie; Chen, Jing (Asian Journal of Chemistry, 2013)
The extraction of palladium(II) from hydrochloric acid medium was carried out using the microspheres containing hexyl benzimidazolyl sulphide as an extractant. Adsorption capacities under optimum conditions were determined. The Pd(II) ions adsorption capacities increased by increased hexyl benzimidazolyl sulphide content and initial Pd(II) ions concentration and it reached the maximum value at 0.4 g L-1 initial Pd(II) ions concentration under the determined optimum conditions. Successful striping of palladium(II) from the microspheres were achieved with 0.8 mol L-1 thiourea solution. The microspheres can be reused at least in 20 cycles of extraction-stripping process.